Mechanistic Insights into the Post‐Cyclization Isomerization in Gold‐Catalyzed 7‐exo‐dig‐Hydroarylations. Issue 32 (26th June 2015) - Pflästerer, Daniel; Schumacher, Sören; Rudolph, Matthias; Hashmi, A. Stephen K.
Abstract: The subsequent double‐bond isomerization in the synthesis of dibenzocycloheptenes and their heteroaromatic analogues was investigated. In the case of biphenyls, a basic additive completely prevented an isomerization to the thermodynamic product. With electron‐rich intramolecular heteroaromatic nucleophiles, the isomerization was still observed, but the kinetic product can be obtained by careful control of the reaction times in most cases. Mechanistic studies demonstrated that a slow isomerization is also possible with the gold catalyst at elevated temperatures, but much faster isomerization rates were observed with acidic additives. An observed initiation period for the gold‐catalyzed isomerization indicates that not the homogenous catalyst, but a decomposition product of it may be the catalytically active species. Abstract : Homogeneous catalysis : The subsequent double‐bond isomerization in the synthesis of dibenzocycloheptenes and their heteroaromatic analogues was investigated. In the case of biphenyls, a basic additive completely prevented an isomerization to the thermodynamic product (see scheme).